Smallholder farmers’ attitudes and determinants of adaptation to climate risks in East Africa - Shikuku, Kelvin Mashisia; Winowiecki, Leigh Ann; Twyman, Jennifer; Eitzinger, Anton; Pérez, Juan Guillermo; Mwongera, Caroline; Läderach, Peter R.D. (Elsevier, 2017)
Adapting to climate risks is central to the goal of increasing food security and enhancing resilience of farming systems in East Africa. We examined farmers’ attitudes and assessed determinants of adaptation using data from a random sample of 500 households in Borana, Ethiopia, Nyando, Kenya, Hoima Uganda, and Lushoto, Tanzania. Adaptation was measured using a livelihood-based index that assigned weights to different individual strategies based on their marginal contributions to a household’s livelihood. Results showed that farmers’ attitudes across the four sites strongly favored introduction of new crops, changes in varieties, and changes in planting times. Farmers disfavored soil, land, and water management practices. At lower levels of adaptation (25% quantile), adaptation index correlated positively with membership to farmers’ groups, household size, sex of the household, and number of months of food shortage. Membership to farmers’ groups enhanced adaptation at intermediate (50% quantile) level whereas access to credit increased adaptation at high (75% quantile) level. Food insecurity, however, correlated negatively with the likelihood to choose individual adaptation strategies suggesting that although households adapted to improve food security status of their households, hunger was a barrier to adaptation. Our findings suggest that providing climate information to inform timely planting, promoting crop diversification, and encouraging adoption of adapted varieties of crops might be successful to enhancing resilience of farming systems in the short-term. In the long-term, increased investment in reducing hunger, encouraging groups formation, and easing liquidity constraints will be required to promote adaptation through implementation of soil, water, and land management strategies